PENERAPAN FAILOVER NETWORK MENGGUNAKAN JARINGAN VPN DAN JARINGAN WIRELESS POINT-TO-POINT PADA DISTANCE BUILDING DI PT. TITIPAN KILAT RIAU - Afdhil Hafid; Harun Mukhtar; Dani Harlian (P3M Politeknik Negeri Indramayu, 2023)
This research is intended to build a network that that can connect branch offices with main office buildings in a company. This is done in order to create all performance connected to a company network that can improve and run well, so as to be able to support the company's business processes. At the stage of meeting company needs and in an effort to overcome problems in the network used technology that can always be online with the expectation of quality of services (QoS) approaching 100%.. The technology applied uses two communication lines, the first connection line is point-to-point wireless and the second connection line applies a Virtual Private Network (VPN) with the use of the internet. Handles failover on both network communication connections used by the mikrotik router. This allows if one connection is lost, the other connection line will automatically become a backup line. In this failed network simulation, it shows satisfactory results, as can be seen from the communication performance that runs without feeling tired of traffic. The application of this method can also operate without involving humans. In addition, the results of the measurement of the time lag required for switching connection lines have an average delay value of not more than 4.97 seconds.